Micro-Computed Tomography Derived Anisotropy Detects Tumor Provoked Deviations in Bone in an Orthotopic Osteosarcoma Murine Model - Cole, Heather A.; Ohba, Tetsuro; Ichikawa, Jiro; Nyman, Jeffry S.; Cates, Justin M. M.; Haro, Hirotaka; Schwartz, Herbert S.; Schoenecker, Jonathan G. (PLOS ONE, 2014)
Radiographic imaging plays a crucial role in the diagnosis of osteosarcoma. Currently, computed-tomography (CT) is used to measure tumor-induced osteolysis as a marker for tumor growth by monitoring the bone fractional volume. As most tumors primarily induce osteolysis, lower bone fractional volume has been found to correlate with tumor aggressiveness. However, osteosarcoma is an exception as it induces osteolysis and produces mineralized osteoid simultaneously. Given that competent bone is highly anisotropic (systematic variance in its architectural order renders its physical properties dependent on direction of load) and that tumor induced osteolysis and osteogenesis are structurally disorganized relative to competent bone, we hypothesized that μCT-derived measures of anisotropy could be used to qualitatively and quantitatively detect osteosarcoma provoked deviations in bone, both osteolysis and osteogenesis, in vivo. We tested this hypothesis in a murine model of osteosarcoma cells orthotopically injected into the tibia. We demonstrate that, in addition to bone fractional volume, μCT-derived measure of anisotropy is a complete and accurate method to monitor osteosarcoma-induced osteolysis. Additionally, we found that unlike bone fractional volume, anisotropy could also detect tumor-induced osteogenesis. These findings suggest that monitoring tumor-induced changes in the structural property isotropy of the invaded bone may represent a novel means of diagnosing primary and metastatic bone tumors.